Does the Phillips curve exist? Evidence from the Middle East and North African Countries - Muhammad Azam; Rasheed Khan; Saleem Khan (Journal of Central Banking Theory and Practice, 2022)
This study aims to explore the validity of Phillips curve for eight (8) countries from the Middle East and North Africa (MENA), namely Algeria, Egypt, Jordan, Kuwait, Malta, Morocco, Saudi Arabia, and Tunisia over the period of 1991-2019. The panel autoregressive distributed lag/pooled mean group (ARDL/PMG) estimation is employed in the study because of the nature of data. The results of ARDL/PMG reveal that there is no trade-off between inflation and unemployment rates in the panel of eight MENA countries in the long run, while there is a negative but insignificant relationship between these two variables in the short run. In addition, the trade-off between inflation and unemployment for each of the panel's countries has also been investigated. The empirical results indicate that there is no trade-off in the short run as the estimated coefficients found are statistically insignificant. Hence, it is concluded that there is no empirical evidence of the trade-off between inflation and unemployment rates in MENA countries.
Keywords: E31; E24; N15; 330; nflation rates; unemployment rates; Phillips curve; ARDL/PMG; MENA-8